Ectopic mouse TMC1 and TMC2 alone form mechanosensitive channels that are potently modulated by TMIE - Yixuan Chen; Yulin Li; Yonghong Liu; Jiawen Sun; Wanying Feng; Yanfei Chen; Ye Tian; Tianlun Lei; Pingbo Huang (Proceedings of the National Academy of Sciences, 2025)
The mechanotransduction (MT) channel expressed in cochlear and vestibular hair cells converts the mechanical stimulation of sound and head movements into electrochemical signals. Recently, TMC1 and TMC2 (TMC1/2) have been recognized as the pore-forming subunit of the MT channel, but TMC1/2 functional expression in heterologous cells—which is critical for unequivocally identifying them as the bona fide pore-forming subunit of the MT channel—has not been achieved because ectopic TMC1/2 become trapped in the ER. Here, we report that adding a Fyn lipidation tag to mouse TMC1/2 (mTMC1/2) drove their cell-surface expression, and, importantly, full-length mTMC1/2 expressed alone functioned as mechanosensitive channels, underscoring the view that TMC1/2 constitute the sole pore-forming subunit of the MT channel. Moreover, mouse transmembrane inner ear (TMIE) (mTMIE) protein robustly stimulated TMC1/2 channel activity by modulating their gating. Intriguingly, the N-terminal 27 residues of mTMIE were dispensable for regulating TMC1/2 in our in vitro functional assay, whereas, in striking contrast, mutating mTMIE C76C77, the predicted palmitoylation sites, eliminated mTMIE stimulation of mTMC1/2, indicating a crucial role of the palmitoyl group in regulating TMC1/2 gating. mTMC1/2+mTMIE form 18 pS and 24 pS single channels, respectively. mTMC1/2+mTMIE single channels showed biophysical and pharmacological properties similar to those of the MT channel. Our findings provide insights into several fundamental and debated aspects of the function of TMC1/2 and TMIE, and our functional assay of TMC1/2 and TMIE in heterologous cells will facilitate further functional and structural characterization of these proteins and other MT-complex components.